Biotransformasi Pirokatekol Glikosida Menggunakan Kultur Suspensi Sel Solanum mammosum L. - Yati Sudaryati Soeka; Joko Sulistyo (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
A syntesis of pyrocathecol glucoside was carried out by applying biotransformation cell culture suspension from calus of Solanum mammosum L., on modified medium of Murashige and Skoog (MS). A growth maximum volume at 15,5 ml of cell culture suspension of S. mommosum was achieved on day-8 incubation. The results showed that pyrocathecol glucoside as a bitransformation product that was obtained by application of Pyrocathecol at 50-200 ppm was determined by TLC and identified at Rf value of 0.82−0.83. Futhermore, the biotransformation products were determined by HPLC obtained from the cell culture suspension at concentration of 200 ppm pyrocathecol so that resulted in reaction products based on standard solution. The peaks number 1, 2 and 3 with retention time 2.53 min, 4.62 min and 7.58 min were appropriate to the retention time cellobiose, glucose and methyl α-glucoside, respectively. Peak number 4 with retention time 8.52 min conformed to pyrocathecol-glucobioside as a product of side transfer and peak number 5 with retention time 10.52 min in line with the retention time of arbutin were pyrocathecol-glucoside as a transfer product expected from the result of biotransformation.